2012
DOI: 10.1037/a0025767
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic interracial interactions: A meta-analysis.

Abstract: This meta-analysis examined over 40 years of research on interracial interactions by exploring 4 types of outcomes: explicit attitudes toward interaction partners, participants' self-reports of their own emotional state, nonverbal or observed behavior, and objective measures of performance. Data were collected from 108 samples (N = 12,463) comparing dyadic interracial and same-race interactions, predominantly featuring Black and White Americans. Effect sizes were small: Participants in same-race dyads tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 243 publications
(258 reference statements)
8
111
0
1
Order By: Relevance
“…Target individuals in diverse groups were rated more anxious (M = 3.53, SD = 0.83) than those in racially-homogeneous groups (M = 3.33, SD = 0.81). This finding is consistent with research showing that interracial interactions tend to be anxiety-provoking for White people (Toosi et al, 2012). There was also a significant main effect of gender, F(1,40) = 8.22, p = .007, indicating that female group members were seen as more anxious than male group members.…”
Section: Anxietysupporting
confidence: 92%
See 1 more Smart Citation
“…Target individuals in diverse groups were rated more anxious (M = 3.53, SD = 0.83) than those in racially-homogeneous groups (M = 3.33, SD = 0.81). This finding is consistent with research showing that interracial interactions tend to be anxiety-provoking for White people (Toosi et al, 2012). There was also a significant main effect of gender, F(1,40) = 8.22, p = .007, indicating that female group members were seen as more anxious than male group members.…”
Section: Anxietysupporting
confidence: 92%
“…Specifically, White individuals are often concerned with being perceived as racist by members of other groups (Crandall & Eshleman, 2003;Monteith, Sherman, & Devine, 1998;Shelton & Richeson, 2006), a concern that arises spontaneously given the likelihood of evaluation by an outgroup member (Vorauer, Hunter, Main, & Roy, 2000;Vorauer, Main, & O'Connell, 1998). When interacting with other-race partners, White individuals report more anxiety and discomfort than when interacting with same-race partners (Toosi, Babbitt, Ambady, & Sommers, 2012;Trawalter & Richeson, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…The range of inter-rater reliability in the current study is acceptable and is consistent with the range found in recent meta-analytic work with adults (αs = .64–.98; Toosi, Babbit, Ambady, & Sommers, 2012). …”
supporting
confidence: 90%
“…experimenter bias, publication bias etc.). Notably, Redick et al’s [40] trial also shares in common with the current study, the failure to find near-transfer of training to measures of WM span, or WM capacity, contrary to many findings to this effect in the literature [28, 4950]. …”
Section: Discussionsupporting
confidence: 47%